Inplementation of PCM Coding and Decoding Algorithm Based on C Language - Wang, Yue; Wang, Zhenyu; Li, Xiaozhuo; Xie, Jianghuan; Qu, Kai (2020 3rd International Conference on Advanced Electronic Materials, Computers and Software Engineering (AEMCSE), 2020)
In order to solve the problem that the A-law 13 polyline coding algorithm lacks a specific programming language simulation, C language is used to implement the algorithm in this paper. First, the polar code is obtained according to the positive and negative sample values. Then the paragraph code and the inner code are obtained and finally decoded. Experimental results show that the program can realize A-law 13 polyline encoding and decoding, and for a given sample value, it can obtain its 8-bit encoding. Compared with the bit-wise encoding method, the program is more efficient.